2019
DOI: 10.1108/ccsm-02-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and contextual influences on corporate social responsibility

Abstract: Purpose The purpose of this paper is to examine the influence of managerial cultural values and the contextual environment (country of origin and country of operation) on corporate social responsibility (CSR) investments in three Asian countries. Design/methodology/approach A total of 150 questionnaires were collected from 150 companies located in Taiwan, Malaysia and Singapore. The potential influence of ethnicity on cultural values was controlled by collecting data from ethnic Chinese managers. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 69 publications
(118 reference statements)
0
25
0
1
Order By: Relevance
“…Previous research has paid special attention to how national culture determines specific decisions made by managers. For example, cultural characteristics have been found to influence the type of corporate investment made by firms (Shao et al, 2013), the adoption of codes of good governance (Haxhi and Van Ees, 2010), corporate social responsibility investments (Ling, 2019), the commitment to unprofitable projects (Fehrenbacher et al, 2018), and compensation practices based on status, performance, social benefits and employee ownership plans (Schuler and Rogovsky, 1998). Exploring how culture affects the adoption of ISO 14001 may refine our knowledge about the consequences of culture on strategic choices, in general, and on the diffusion of environmental standards, in particular.…”
Section: Ccsm 264mentioning
confidence: 99%
“…Previous research has paid special attention to how national culture determines specific decisions made by managers. For example, cultural characteristics have been found to influence the type of corporate investment made by firms (Shao et al, 2013), the adoption of codes of good governance (Haxhi and Van Ees, 2010), corporate social responsibility investments (Ling, 2019), the commitment to unprofitable projects (Fehrenbacher et al, 2018), and compensation practices based on status, performance, social benefits and employee ownership plans (Schuler and Rogovsky, 1998). Exploring how culture affects the adoption of ISO 14001 may refine our knowledge about the consequences of culture on strategic choices, in general, and on the diffusion of environmental standards, in particular.…”
Section: Ccsm 264mentioning
confidence: 99%
“…Many research studies have been conducted in economically developed countries, although only a limited number of studies on CSR have taken place in transitional and post-transitional countries (Fifka & Pobizhan, 2014). In countries with fast economic growth (Wu, 2013), or in those with economic systems in the process of transition and adaptation to new legislation, new business practices, and the multinational market, companies may have serious problems understanding CSR and its role in sustainable business models (Stoian & Zaharia, 2012;Doh et al, 2015;Amodu, 2018;Ling, 2019). Also, researchers have shown that national culture values have a significant impact on the attitudes over the organizational culture (Taras et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, konteksnya (negara asal dan negara perusahaanoperasi) juga membedakan nilai budaya dan investasi CSR di ketiga negara ini (Taiwan, Malaysia and Singapore). [24] Berbeda dengan penelitian di jurnal lain, penelitian ini menyebutkan bahwa etika perusahan merupakan fakto rutama yang memotivasi organisasi untuk terlibat dalam kegiatan CSR. Jurnal ini mengungkapkan walaupun ada beberapa faktor yang dapat mempengaruhi implementasi CSR di organisasi seperti kebijakan pemerintah, globalisasi, pelanggan dan investor, kelompok sosial dan lingkungan, maju dalam teknologi komunikasi, namun dalam penelitian ini, etika perusahaan merupakan faktor utama yang dapat memotivasi organisasi untuk terlibat dalam kegiatan CSR.…”
Section: Hasil Dan Pembahasanunclassified